2017
DOI: 10.1037/men0000055
|View full text |Cite
|
Sign up to set email alerts
|

The influence of conventional masculine gender role norms on parental attitudes toward seeking psychological services for children.

Abstract: Paternal involvement in parent training programs has been associated with greater maintenance of treatment gains, lower attrition rates, and less maternal stress. However, male caregivers are less likely to participate in behavioral parent training (BPT) programs than female caregivers. The present study examined (a) the differences between mothers and fathers in their attitudes toward seeking help for their children, and (b) whether parents’ adherence to masculine gender role norms mediated the proposed relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
(148 reference statements)
0
9
0
Order By: Relevance
“…In addition, because previous measures of quality have been developed primarily with mothers, we do not know if these processes work similarly with fathers. Moreover, there is some evidence that masculinity norms can inhibit engagement in services (Cusack, Deane, Wilson, & Ciarrochi, 2006; Triemstra, Niec, Peer, & Christian-Brandt, 2016). Consequently, the presence of gender differences with respect to the influence of fidelity and quality is an exploratory question in this study.…”
Section: Parent Gendermentioning
confidence: 99%
“…In addition, because previous measures of quality have been developed primarily with mothers, we do not know if these processes work similarly with fathers. Moreover, there is some evidence that masculinity norms can inhibit engagement in services (Cusack, Deane, Wilson, & Ciarrochi, 2006; Triemstra, Niec, Peer, & Christian-Brandt, 2016). Consequently, the presence of gender differences with respect to the influence of fidelity and quality is an exploratory question in this study.…”
Section: Parent Gendermentioning
confidence: 99%
“…A few social workers identified the maternal focus of their clinical settings and the challenge of meaningfully infusing fathers into the therapy dynamic under these structural conditions, as a significant challenge. Some research has, therefore, suggested that clinicians employ elements of cognitive behavior therapy and psychoeducation to assist fathers in recognizing their importance to the child, and the family system, while also encouraging fathers to continue to challenge the masculine (Phares et al, 2010;Triemstra et al, 2017) to improve involvement. This process may look remarkably different for varying subsets of fathers, so social workers, and clinicians more broadly, need to be prepared for these potential differences.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 30 years, increasing attention has been directed to understanding the benefits of the father role (Marsiglio et al, 2000) for children, families, and for fathers themselves (Frank et al, 2015;Triemstra et al, 2017). Our understanding of the role of fathers in psychological services has only recently begun to garner some attention, but the literature is still very limited.…”
Section: Fathers In Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These attitudes, most commonly measured by the Attitudes Toward Seeking Professional Psychological Help scale (ATSPPH; Fischer & Turner, ), have been investigated by researchers in numerous studies. Scores on the ATSPPH have been found to be correlated with various factors, including gender (Fischer & Turner, ; Park & Hatchett, ), stage of change in the transtheoretical model (Young, ), race/ethnicity (Al‐Darmaki, ), and masculine gender roles (Triemstra, Niec, Peer, & Christian‐Brandt, ).…”
mentioning
confidence: 99%